O Programa Jovens Empreendedores Primeiros Passos do Sebrae e a divulgação do empreendedorismo na Educação - Camargo, Gabrieli Boenke de (2018)
The entrepreneurship ideology has been highlighted in the educational field through recent years and it is giving education a business character. Hence, the need to question this ideology in order to understand what entrepreneurship is, in what this "educational ideology" is based on and what is Competence Pedagogy? Finally, what is the Young Entrepreneurs First Steps course and how does it deal with the entrepreneurship ideology? To answer these questions, the general objective is to analyze the material proposed by the SEBRAE program called: Jovens Empreendedores Primeiros Passos - JEPP (Young Entrepreneurs First Steps), responsible for the dissemination of entrepreneurial ideology in basic education schools. The main objectives are: to investigate international guidelines for entrepreneurship and the pedagogy of competencies; to point out the relations between entrepreneurship and the pedagogy of competences in basic education; analyze SEBRAE’s JEPP course, understanding how the material deals with the ideology of entrepreneurship in basic education schools. The research is organized into four chapters: in the first, there are some considerations about the world of work, the state and social policies; in the second, the World Bank and its influences on basic education are discussed; in the third, the competence pedagogy as a reproduction of the world of work is presented; and in the fourth, the Young Entrepreneurs First Steps course is explained. For the development of the research, a bibliographical and documentary investigation was carried out both using primary and secondary sources, considering the social, cultural, economic and political elements fundamental to the research.